The relationship between flat foot and lower limb muscle strength in teenage basketball athletes - Ni Luh Kadek Cindy Pratika Dewi; Sayu Aryantari Putri Thanaya; I Putu Yudi Pramana Putra; Anak Agung Gede Angga Puspa Negara (Universitas Udayana dan Diaspora Taipei Medical University, 2024)
Background: Teenage basketball athletes may experience problems with lower limb muscle strength, which can affect their performance due to factors such as the shape of the arches pedis, muscle length and shortness, fatigue levels, muscle contraction ability, and the presence of flat feet, where the medial arch is flattened against the ground. This study aimed to determine the relationship between flat feet and lower limb muscle strength in adolescent basketball athletes in Tabanan Regency. Methods: This study's design was observational analytic with a cross-sectional study direction. It was conducted at junior high and high schools in Tabanan Regency and involved 62 teenage basketball athletes. The inclusion criteria were basketball athletes with flat feet aged 14-17, while the exclusion criteria were a history of fracture or lower limb injury. Lower limb muscle strength was measured using a leg dynamometer, while flat foot was assessed using a wet footprint test. Results: The result of the association test using Spearman’s Rho Test obtained a correlation coefficient value (r) -0.173, which means a unidirectional relationship with a very weak correlation level with a p-value=0.180 (p<0.05), which means there is no significant relationship. Conclusion: There was no relationship between flat foot and lower limb muscle strength in teenage basketball athletes. The correlation coefficient value indicates a unidirectional relationship with a very weak correlation level.